Violent rituals of the Hebrew Bible - Olyan, Saul M. (Oxford University Press USA - OSO, 2019)
Although seldom studied by biblical scholars as a discrete phenomenon, ritual violence is mentioned frequently in biblical texts. Violent Rituals of the Hebrew Bible is the first book to investigate violent rites, the ritual settings in which they occur, their various literary contexts, and the identity and aims of their agents in order to speak in an informed way about the contours and social aspects of ritual violence as it is represented in the Hebrew Bible.